2003
DOI: 10.1016/s0022-5223(03)00389-1
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular to pulmonary artery conduit instead of modified Blalock-Taussig shunt improves postoperative hemodynamics in newborns after the norwood operation

Abstract: A higher diastolic blood pressure and a lower Qp/Qs ratio were associated with a more stable and efficient circulation in patients with a right ventricular to pulmonary artery conduit. More intensive ventilatory support was necessary during the first postoperative days. We did not note any adverse effects of the ventriculotomy on ventricular performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 9 publications
1
95
1
Order By: Relevance
“…We have recently shown that these encouraging early signs may be translated into improved right ventricular performance in the convalescent phase. 26 Clearly 26 catheterisation data of others, 25 and increased survival to stage 2 palliation 23 would all suggest improved, rather than diminished right ventricular function in patients with a conduit.…”
Section: Right Ventricle To Pulmonary Artery Conduit: a Recent Modifimentioning
confidence: 98%
“…We have recently shown that these encouraging early signs may be translated into improved right ventricular performance in the convalescent phase. 26 Clearly 26 catheterisation data of others, 25 and increased survival to stage 2 palliation 23 would all suggest improved, rather than diminished right ventricular function in patients with a conduit.…”
Section: Right Ventricle To Pulmonary Artery Conduit: a Recent Modifimentioning
confidence: 98%
“…This would suggest that, in our hands, these patients would have had a better outcome with a standard Norwood approach. The classical Norwood procedure, using a systemicpulmonary shunt, has been criticised for similar reasons in terms of the continuous diastolic flow [9], but has not been associated with such profound diastolic hypotension or reversed diastolic flow. This may be because the haemodynamic effects of an unrestrictive AP window are more dramatic than those of a Gore-Tex shunt (which is both more peripheral in the circulation, narrower and longer, resulting in an inbuilt degree of fixed resistance which helps to dampen the degree of diastolic run-off).…”
Section: Discussionmentioning
confidence: 99%
“…Several case series report improved short-term survival with the Sano modification [1,3,9,10]. Retrospective reviews have demonstrated no early or midterm survival differences between the mBTS or the Sano modification [4,[11][12][13].…”
mentioning
confidence: 99%